Product Recalls and Stock Market Reaction: Empirical Evidence from the Pharmaceutical Industry in the UK And USA - Chieng, Corinne Lin Lin (2005)
This dissertation attempts to study and understand stock reaction upon product recalls in the United Kingdom (UK) and United States of America (USA) pharmaceutical industry by employing the event study methodology. Drawing on the growing importance and repercussions from product recalls in the pharmaceutical industry on societys wellbeing, the focus of this study intends to ascertain if there were negative stock reactions accompanied by significant abnormal returns upon recall announcements. In addition, this study investigates whether the act of product recall, being a subset of Corporate Social Responsibility (CSR), would significantly affect a CSR advocate comparatively in terms of variation in the degree of stock reaction as compared to a non-CSR advocate in accordance to its inclusion on the FTSE4Good Index and Dow Jones Sustainability Index (DJSI). Finally, the study aims to examine if the dissemination of new information is efficient in the stock market during these announcements. This event study was embarked on by collating data from listed pharmaceutical firms in the UK and USA respectively, which had product recall announcements for the years 1998 to 2004 and was further segregated and analysed individually as different recall classes. This study was further substantiated by the Corrado (1989) rank test for smaller samples. It was observed in the findings that there existed negative stock reaction upon product recalls for all classes of recalls, though not significant on announcement days. Exceptional findings were noted for product recalls of moderate risk whereby positive post-announcement stock reactions suggested that product recalls were viewed favourably as an act of good CSR practice. The delayed stock reactions during post-announcement periods indicated some form of market inefficiency. From an ethical and legal CSR perspective, the practice of product recalls did not result in less adverse stock reactions and there were no significant variation in results between CSR and non-CSR advocates in both countries. Comparatively, the results were clearly mixed and the magnitude of stock reactions was observed to be greater in the UK as compared to the USA. Possible explanation for the findings noted were directed towards the differing public policies adopted in promoting CSR, differing market capitalisation levels and emerging Socially Responsible Investment (SRI) developments. The role of government regulation and legal obligations as an intervening factor towards stock reaction on product recalls as implicated in this study remains an interesting notion that warrants further attention in future researches. Replication of this event study could further be extended to myriad industries and countries with varying degrees of development to determine if investors reactions towards product recalls were similar. Viewing the evolving CSR development and the mixed stock reactions on pharmaceutical product recalls, it is evident that the market perception and attitude towards CSR remain varied. Efforts to inculcate CSR awareness amongst stakeholders of firms, which includes but not limited to investors, should remain the focus in appreciation of the benefits attached therewith.